2012
DOI: 10.1155/2012/795439
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia and Risk of Adverse Bleeding Effect of Drugs: Implication for Therapy

Abstract: This study aimed to evaluate the progress in reduction of prevalence of anemia in rural Australia. It also investigates the prevalence of hypoviscosity in anaemia with a view to determine the fraction of anaemic patients at risk of drug-inducible exacerbation of anemia. Archived clinical pathology data (N = 130, 354) for the period of 1999 to 2008 were utilized. The prevalence of anemia and hypoviscosity was evaluated by working out (i) the number that fell within anemia definition as a percentage of the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It is essential for females who are pregnant to keep their Hemoglobin and Iron levels checked and to intimate their caretakers if they have one or more symptoms of anemia. (30) Iron and Vitamin B12 supplements can be taken regularly which may help prevent low iron levels and pregnancy-related anemia. In the study, the most commonly observed range of Hemoglobin level is 12-13g/dl with a frequency of 26.6% followed by 11-12g/dl with a frequency of 22.9%.…”
Section: Resultsmentioning
confidence: 99%
“…It is essential for females who are pregnant to keep their Hemoglobin and Iron levels checked and to intimate their caretakers if they have one or more symptoms of anemia. (30) Iron and Vitamin B12 supplements can be taken regularly which may help prevent low iron levels and pregnancy-related anemia. In the study, the most commonly observed range of Hemoglobin level is 12-13g/dl with a frequency of 26.6% followed by 11-12g/dl with a frequency of 22.9%.…”
Section: Resultsmentioning
confidence: 99%